The Role of Agriculture and Rural Training Center of Karya Tani and Its Relationship With Farmer’s Behavior In The Development Of Porang Nursery In Tanjung Batu Village Ogan Ilir Regency - Emmanuel Pinem, Andre Ignatius; Wildayana, Elisa (Departement of Socio-Economic Agricuture, Faculty of Agriculture, 2022)
ABSTRACT Agriculture and Rural Training Center (ARTC) Karya Tani is an institution in the field of education and rural owned and managed independently both individuals and groups and is not a government agency. Seeing the potential offered by the porang plant as an effort to increase income because it has a high economic value and is very tolerant of shade, rubber farmers who are members of the P4S Karya Tani Tanjung Batu institution began to cultivate porang nurseries as a rubber interplant. This thesis aims to 1) identify the role of Agriculture and Rural Training Center (ARTC) Karya Tani in the development of porang nurseries in Tanjung Batu village, 2) identify the level of behavior of farmers who attend training in agricultural and Rural Training Center (ARTC) Karya Tani in Tanjung Batu village, and 3) analyze the relationship of the role of Agriculture and Rural Training Center (ARTC) Karya Tani with farmer's behavior in the development of porang nurseries in Tanjung Batu village. The method used in this study is the survey method. Determination of samples in this study using purposive sampling method, with the number of samples used amounted to 30 farmers. The results of this thesis are 1) Agriculture and Rural Training Center (ARTC) Karya Tani has utilized well as educators, as a source of information and experience, and as a source of social shaping, the total calculation is on high criteria with a total score of 24.96, 2) the behavior of farmers who have attended training in Agriculture and Rural Training Center (ARTC) Karya Tani is on high criteria based on the calculation obtained a total score of 15.62, 3) based on the Spearman Rank correlation test, it can be concluded that the role of Agriculture and Rural Training Center (ARTC) by farmers affects the behavior of farmers in the development of porang nurseries in Tanjung Batu Village. Keyword: porang nursery, training role, farmer’s behavior